Detección de Anticuerpos contra Ehrlichia spp en Propietarios de Caninos Domésticos con Ehrlichiosis - Gómez M., Beatriz (2017)
The seroreaction of Ehrlichia chaffeensis through the indirect immunofluorescence test (IFI) was determined in owners of dogs with a history of ehrlichiosis. In addition, the association with gender, age, exposure to ticks and level of contact with dogs was evaluated. The study was conducted between January and December 2009, where 95 people from Lima Metropolitan Region (Peru) were evaluated, regardless of gender, age or socioeconomic status, and whose dogs had a history of ehrlichiosis of less than one year. The results showed that 31.6% (30/95) of dog owners presented antibodies against E. chaffeensis. Besides, 38.7% (24/62) of the individuals younger than 40 years and 18.2% (6/33) of individuals older than 40 years were seropositive to E. chaffeensis (p<0.05), 29.4% of males and 32.7% of females were seropositive to E. chaffeensis (p<0.05), and 40.0 and 8.0% of those exposed and not exposed to arthropods presented seropositivity to this pathogen.